Comparison of thrombomodulin, vWF, and ADAMTS13 levels between preeclampsia and normal pregnancy - Ahmad, Aisha; Mustafa , Ghulam; Mazari, Nazish; Asif , Muhammad (Journal of the Pakistan Medical Association, 2023)
Objective: To determine and compare plasma thrombomodulin, von Willebrand factor and von Willebrand factor-cleaving protease levels between pre-eclamptic and healthy pregnant females. Method: The cross-sectional, comparative study was conducted at the Department of Haematology, University of Health Sciences, Lahore, Pakistan, from November 2019 to December 2020, and comprised pregnant females who were divided into healthy pregnant group A and pre-eclamptic group B. Plasma thrombomodulin and von Willebrand factor-cleaving protease levels were determined by using commercially available enzyme-linked immunosorbent assay kit, and von Willebrand factor level was determined by using immuno-turbidimetric assay kit. Data was analysed using SPSS 25. Results: Of the 88 participants, there were 44(50%) females with mean age 25.5±6 years in group A and 44(50%) in group B with mean age 26±5 years. Median thrombomodulin level in group B was significantly higher than group A (p=0.003). Median von Willebrand factor-cleaving protease levels were lower in group B compared to group A (p=0.838). A significant difference in von Willebrand factor level was observed between the groups (p=0.038). Conclusion: Females with pre-eclampsia had significantly higher plasma levels of von Willebrand factor and thrombomodulin than healthy pregnant subjects. Key Words: Thrombomodulin, vWF, ADAMTS13 protein, Pre-eclampsia.